Pengaruh Intensitas Konten Tiktok Terhadap Kesehatan Mental Mahasiswa Generasi Z: (Studi Kuantitatif pada FISIP Universitas Muhammadiyah Makassar) - friska; Arni; Ilham Riyadi (Jurnal Komunikasi dan Organisasi (J-KO), 2025)
Social media allows users to share, interact, and create content. TikTok is one of the most popular social media platforms in Indonesia, especially among teenagers, millennials, and Gen Z. Therefore, this study aims to analyze the influence of TikTok usage intensity on the mental health of Generation Z students at Muhammadiyah University of Makassar. This study further examines how internal and external factors are crucial to understanding how TikTok influences user behavior. The research method used a quantitative approach with 95 respondents selected through a stratified random sampling technique. Data were collected through a Likert scale questionnaire and analyzed using the Pearson correlation test and simple linear regression. The results showed a significant relationship between the duration of TikTok use (1–3 hours per day) and increased anxiety and stress. The use of TikTok as a social media platform among students who are active on TikTok has an impact on life satisfaction and mental health. These findings support the Social Comparison and Uses and Gratifications theories, and demonstrate the importance of digital literacy and time management in using social media to maintain student mental health.